The effects of alcohol on ambulatory blood pressure and other cardiovascular risk factors in type 2 diabetes: A randomized intervention - Mori, T.; Burke, V.; Zilkens, Renate; Hodgson, J.; Beilin, L.; Puddey, I. (Lippincott Williams & Wilkins, 2016)
Objective: Although prospective studies suggest light-to-moderate chronic alcohol intake protects against coronary artery disease in type 2 diabetic patients, the balance of effects on individual cardiovascular risk factors needs further assessment. We examined the effects of alcohol consumption on 24-h ambulatory blood pressure (BP) and heart rate (HR), high-density lipoprotein cholesterol, fibrinogen, C-reactive protein, homocysteine, and glycaemic control in well controlled type 2 diabetes. Methods: Twenty-four participants aged 49-66 year were randomized to a three-period crossover study with women drinking red wine 230ml/day (~24g alcohol/day) and men drinking red wine 300ml/day (~31g alcohol/day), or equivalent volumes of dealcoholized red wine (DRW) or water, each for 4 weeks. Ambulatory BP and HR were monitored every 30min for 24h at the end of each period. Home blood glucose monitoring was carried out twice weekly throughout. Results: Red wine increased awake SBP and DBP relative to water by 2.5±1.2/1.9±0.7mmHg (P=0.033, P=0.008, respectively), with a similar nonsignificant trend relative to DRW. Asleep DBP fell with red wine relative to DRW (2.0±0.8mmHg, P=0.016) with a similar nonsignificant trend relative to water. Red wine increased 24-h, awake and asleep HR relative to water and DRW. Relative to DRW, red wine did not affect glycaemic control or any other cardiovascular risk factor.Conclusion: In well controlled type 2 diabetic individuals 24–31 g alcohol/day (∼2–3 standard drinks) raises awake BP and 24-h HR and lowers asleep BP but does not otherwise favourably or adversely modify cardiovascular risk factors.